A new species of Macrophthalmus Desmarest, 1823 (Crustacea: Decapoda: Brachyura: Macrophthalmidae) from Taiwan, with notes on four new records - Teng, Shao-Jyun; Shih, Hsi-Te (Zootaxa, 2015)
A new species of sentinel crab (family Macrophthalmidae), Macrophthalmus (Mareotis) purpureocheir sp. nov., from coral reefs is herein described from southern and eastern Taiwan. The new species can be distinguished from other species by a suite of characters, including the narrower and more convex carapace, the first anterolateral tooth protruding forward, the short and stout chelipeds, and the male first gonopod with short apical process, as well as the distinctive reddish purple chelae of the male. The identity of this new species is also supported by molecular evidence using the mitochondrial 16S rDNA and cytochrome oxidase subunit I (COI). Three additional species of Macrophthalmus, viz. M. crinitus Rathbun, 1913, M. definitus Adams & White, 1849, and M. milloti Crosnier, 1965, as well as Ilyograpsus paludicola (Rathbun, 1909) of the subfamily Ilyograpsinae Števčić, 2005, are also confirmed from Taiwan.